'A little bubble of utopia': constructions of a primary care-based pilot clinic providing gender affirming hormone therapy. Issue 1 (2nd January 2021) - Ker, Alex; Fraser, Gloria; Fleming, Theresa; Stephenson, Cathy; da Silva Freitas, Anny; Carroll, Richard; Hamilton, Thomas K.; Lyons, Antonia C.
ABSTRACT: The provision of gender affirming hormone therapy for transgender and non-binary people is a rapidly developing area of gender affirming healthcare. While research indicates the benefits of providing gender affirming hormone therapy through interdisciplinary primary care-based models, less is known about how service users and providers construct their understandings of affirmative approaches. In this paper, we present findings from a discourse analysis of four service users' and four healthcare professionals' talk about a primary care-based pilot clinic providing gender affirming hormone therapy in Aotearoa New Zealand. Participants employed notions of pathologisation, time, and agency in their talk to construct the clinic as a personal setting which gave service users time to make their own health decisions, while constructing hospitals as impersonal with lengthy wait times. The assessment-driven nature of best practice guidelines that governed clinicians' decision-making was constructed as constraining users' agency. Findings highlight the ongoing importance of aligning gender affirming hormone therapy with other non-disease types of healthcare, and suggest new ways for achieving this through affirmative approaches to healthcare.